Alaska Air One Rescue : One Last Chance - Book 2 - Warren, Susan May, 1966- (Thorndike, Maine : Center Point Large Print, 2024)
"Axel Mulligan was built to be a Coast Guard rescue swimmer. He swam fast and endured long, a miracle for those in peril -- until a tragedy sent him home to Alaska. Now, three years later, hes not going to let the past repeat itself. As an Air One rescue swimmer, he ll do anything to save lives -- including sacrifice his own. He expects to do just that while trying to rescue a group of tourists from the icy waters of the Gulf of Alaska. But if not for the voice on the other end of the ham radio, he might have given up and let hypothermia win. That voice awakened something in his heart, and he sets out to find the woman it belongs to. Flynn Turnquist is not who Axel thinks she is. A national wildlife researcher, shes deep in the bush, tracking wolf pack patterns. Or is she? In fact, shes a former cop, tracking down a serial killer. She nearly had him -- until he escaped into the wilds of the Alaska bush. When Axel finds Flynn and discovers what shes really up to, it stirs up a terrible nightmare hes been dodging for years -- the kidnapping and death of his own cousin. Worse, hes led the killer right to her doorstep. Now, its a race through Alaska to stay alive. And when tragedy strikes again, he must choose between rescue or redemption."--
Keywords: Rescue work -- Fiction; Serial murderers -- Fiction; Wilderness survival -- Fiction; Alaska -- Fiction; large print books; Christian fiction; Thrillers (Fiction); Romance fiction; Large print books